Efecto de una bebida gaseosa sobre el ciclo de vida de Drosophila melanogaster (2016)
Drosophila melanogaster it´s one the experimentally models that has been used as base of study for the consolidations and advances in biology from beginnings of XX century, showing characteristics as length of life cycle short and many offspring, facilitating performing various tests and trials, with the objetive of make a proof about of a fizzy drink effects, (Coca Cola) in the Drosophila melanogaster life cycle. It performed banana farming, distilled water and 10 drops of Nystatin and experimental conditions with dilutions 30 ml water+20 ml of Coca Cola (Treatment 1) 25 ml of water and 25 of Coca Cola (Treatment 2) and 30 ml of Coca Cola + 20 ml of water (Treatment 3) until the fourth generation, each with four reproductions. Followed it, a mathematic pattern based on differential equations with the objective to analyze population behaviour was performed. Lastly, polytene chromosomes extracted from the salivary glands of third instar larvae. It found a reduction in transfers rates and death among treatments generation, phenotypic changes and chromosome fragmentation. Statistically did not show effect of treatment on the life cycle of the biological model presenting a confidence level of 95% (p>0.05). With the results it was concluded that the changes found may be related by the types of components of the Coca Cola® and the concentration at which the flies were exposed